The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1016/s0042-6989(99)00036-x
|View full text |Cite
|
Sign up to set email alerts
|

How does noise influence the estimation of speed?

Abstract: Local motion signals have to be combined in space and time, to yield a coherent motion percept as it is involved in a variety of visual tasks. This combination necessarily means to trade-off between loosing spatio-temporal resolution by pooling local signals and maintaining perceptually significant segmentation between them. When signals are pooled to detect the presence of coherent motion in large amounts of random noise, the question raised is how the noise affects the perceived quality, in particular speed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…At a video frame-rate of 25 Hz, the default time constant was chosen to be 80 ms (two frames), which bestows the EMD with a temporal frequency optimum of approx. 2 Hz (see, e.g., Zanker & Braddick 1999). This tuning is well within the range of temporal frequency characteristics described for a variety of motion sensitive neurones in insects (O'Carroll et al 1997).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…At a video frame-rate of 25 Hz, the default time constant was chosen to be 80 ms (two frames), which bestows the EMD with a temporal frequency optimum of approx. 2 Hz (see, e.g., Zanker & Braddick 1999). This tuning is well within the range of temporal frequency characteristics described for a variety of motion sensitive neurones in insects (O'Carroll et al 1997).…”
Section: Discussionsupporting
confidence: 75%
“…This model has been used previously to analyse species-specific movement signals in crabs (Zeil & Zanker 1997), and to simulate a variety of psychophysical phenomena (Zanker 1997;Zanker & Braddick 1999;Zanker 2004). The basic building blocks of the 2DMD model are elementary motion detectors (EMDs) of the correlation type, which have been shown to describe the computational structure of biological motion detectors at least in insects (for review, see Reichardt 1987;.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the addition of the variability did not lead to an increase or decrease in the perceived stiffness of the force field. This is consistent with the findings of Zanker et al [49] who created different levels of noise in visual speed feedback. They observed that while the noise had no effect on the perceived speed, the noise impacted the certainty.…”
Section: Discussionsupporting
confidence: 92%
“…Unexpectedly, when the CS moved in front of the rDVN with the same physical speed as the SS, the proportion of "CS faster" responses was not above chance (0.5), even when the TMS was applied over the control site Cz. This is important because, statistically speaking, it is not possible to conclude that visual dynamic noise actually enhanced the perceived speed of a target as in previous studies (Edwards & Grainger, 2006;Zanker & Braddick, 1999). 1 On the other hand, in the SVN condition, with rTMS delivered over the Cz (control condition) and with the CS as fast as the SS, the proportion of "CS faster" responses was not below chance (0.5) and the BF (3.55) was clearly in favour of the null hypothesis.…”
Section: Discussionmentioning
confidence: 82%